Calibration of the JUICE RWI Antennas by Numerical Simulation. Issue 11 (10th November 2021) - Fischer, G.; Panchenko, M.; Macher, W.; Kasaba, Y.; Misawa, H.; Tokarz, M.; Wisniewski, L.; Cecconi, B.; Bergman, J.; Wahlund, J.‐E.
Abstract: The reception properties of the Radio Wave Instrument (RWI) onboard JUICE (Jupiter Icy Moons Explorer) have been determined using numerical methods applied to a mesh‐grid model of the spacecraft. The RWI is part of the RPWI (Radio and Plasma Wave Investigation) and consists of three perpendicular dipoles mounted on a long boom. We determined their effective lengths vectors and capacitive impedances of 8–9 pF. We also investigated the change in effective antenna angles as a function of solar panel rotation and calculated the directivity of the antennas at higher frequencies up to the maximum frequency of 45 MHz of the receiver. We found that the RWI dipoles can be used for direction‐finding with an accuracy of 2 ° up to a frequency of 1.5 MHz. Additionally we calculated the influence of strong pulses from the JUICE active radar on RPWI and found that they should do no harm to its sensors and receivers. Plain Language Summary: In this paper we calculate the reception properties of the antennas of the Radio Wave Instrument (RWI) onboard the JUICE (Jupiter Icy Moons Explorer) spacecraft using numerical computer simulations. The RWI is part of the RPWI (Radio and Plasma Wave Investigation) and consists of three perpendicular dipoles mounted on a long boom. With this antenna system the scientists want to determine the intensity, the polarization, and the incoming radio wave direction of Jovian radio emissions. This can only be properly done when the reception properties of the antennas are well known, and for this necessary calibration we calculate the so‐called effective length vector. It can describe the reception properties of an antenna, being constant (direction‐independent) when the wavelength is large compared to the dimensions of the spacecraft. The antenna pattern of an RWI dipole has a toroidal shape like a donut at lower frequencies, but gets multiple lobes at higher frequencies. We also calculated the influence of the strong pulses from the JUICE active radar on the RPWI sensors and receivers and found that no harm should be done to them. Key Points: The antennas of the Radio Wave Instrument (RWI) onboard Jupiter Icy Moons Explorer were calibrated by numerical computer simulations Results include the calculation of effective lengths vectors, antenna impedances, and high‐frequency characteristics Strong active radar pulses should not harm the RWI and Langmuir probe receivers